Tingkat Keterampilan Teknik Dasar Bola Basket Tim Bola Basket SMA Negeri 5 Cirebon - Aldie Zamaludin; Risa Herdiyana Bastian; Fajar Kurniawan; Dewi Wahyuni (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. The purpose of this study is to determine the influence of PJOK lessons on clean and healthy living behavior (PHBS) of grade VI students of SDN Sidorejo. Materials and methods. The research method used by the researcher in this study is a qualitative and quantitative mixed method, with the research design using a sequential exploratory design. The implementation of this research was carried out at SD Negeri Sidorejo, Pekalongan Regency with a population of 180 students, and the number of research samples used was 30 grade VI students. The data collection technique used PJOK and PHBS questionnaires. Results. The results of the study show that PJOK lessons have an influence on the PHBS of grade VI students of SDN Sidorejo, Pekalongan Regency. Conclusion. PJOK lessons not only play a role in increasing students' physical activity, but also have a significant effect on forming clean and healthy living habits (PHBS). Through simple habits applied in schools, PJOK is able to instill students' awareness to maintain their health and the environment in a sustainable manner.